MEMBANGUN MASYARAKAT SADAR NARKOBA: PENYULUHAN BAHAYA NARKOBA DAN IMPELEMENTASINYA PADA KESEHATAN DI KELURAHAN SUKALAKSANA, KECAMATAN CURUG - Kartika, Rika; Alim, Syirozul; Wulansari, Irma; Roby, Febri; Suhartoyo, Suhartoyo (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
Drug abuse can affect the central nervous system, reduce awareness, cause dependence, and negatively impact the physical, mental, and social health of users. However, in this region, there is still a lack of education regarding the dangers of drugs and a lack of preventive measures related to drug use. The purpose of this community service (PKM) activity is to increase public understanding of the types of drugs, the psychological and health impacts of their use, and the legal consequences that accompany drug abuse. This PKM also aims to build collective community awareness in preventing the spread of drugs in their environment. The method of implementation of the activity was carried out in the form of counseling. The results of the activity showed an increase in participants' understanding of the legal, health, and psychological aspects related to drugs. Interactive discussions showed that the community began to understand the importance of prevention and an active role in reporting and rehabilitating users. This activity was concluded to be effective and able to increase public literacy and awareness of the dangers of drugs. Further counseling and collaboration between institutions are highly recommended for the sustainability of education and the creation of a drug-free environment.